2019
DOI: 10.1021/acs.cgd.9b00038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, Photophysical Properties, and Antibacterial Assessment of Silver(I)-Thione Coordination Polymers Based on a Competition between Nitrate Anion and Coanions CF3SO3, ClO4, BF4, PF6, and SbF6

Abstract: Six new coordination polymers, namely, [Ag 2 L-(NO 3 ) 2 ] n (1), {[Ag 6 L 4 (CF 3 SO 3 ) 4 ][CF 3 SO 3 ] 2 } n (2), {[Ag 2 L-(NO 3 )][ClO 4 ]} n (3), {[Ag 2 L(NO 3 )][BF 4 ]} n (4), {[Ag 2 L(NO 3 )]-[PF 6 ]} n (5), and {[Ag 2 L(NO 3 )][SbF 6 ]} n (6), have been successfully synthesized by the reaction of AgNO 3 and selected coanions CF 3 SO 3 − , ClO 4 − , BF 4 − , PF 6 − , and SbF 6− with 1,3-bis(1methylthioimidazolyl) propane under the same experimental conditions in order to illustrate coordination ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Some of the tested silver complexes possess relatively good antimicrobial properties because complexes are mostly bacterial agents that can kill target bacteria at a low concentration. [ 44 ] The high antibacterial potential of these complexes is due to the presence of Ag(I) ion in the structure of complexes which is capable of dismantling the pathogen metabolic pathway via multiple mechanisms. [ 45 ] It has been reported that Ag(I) metallodrugs work by disabling numerous cellular enzymes that are central to respiration and metabolism or by denaturing cellular macromolecules and will eventually inhibit normal cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the tested silver complexes possess relatively good antimicrobial properties because complexes are mostly bacterial agents that can kill target bacteria at a low concentration. [ 44 ] The high antibacterial potential of these complexes is due to the presence of Ag(I) ion in the structure of complexes which is capable of dismantling the pathogen metabolic pathway via multiple mechanisms. [ 45 ] It has been reported that Ag(I) metallodrugs work by disabling numerous cellular enzymes that are central to respiration and metabolism or by denaturing cellular macromolecules and will eventually inhibit normal cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various coordination polymers (CPs), metal organic frameworks (MOFs), and covalent organic frameworks (COFs) have been reported as new candidates for the removal of iodine. ,, In the structure of these polymers, the nature of metals, kind of ligands, counterions, type of solvents, and reaction conditions play a vital role. Alternatively, there is a rapid growth in the manufacturing of the ligands with O, N, and S donor atoms to use in the CPs and MOFs. In particular, the systematic designs of sulfur-containing ligands have been investigated in bioinorganic chemistry and for their ability to create various coordination network architectures. , Following our ongoing research on the development of coordination polymers with S donor ligands, ,, herein, we report four novel metal–organic frameworks with d 10 transition metals of group 12 and L s (pbit) ligand [where L s or pbit = 1,1′-(pentane-1,5-diyl)­bis­(-3-methyl-1 H -imidazole-2-thione)]. The title polymers were applied as an adsorbent for hydrogen sulfide and also used for iodine removal.…”
Section: Introductionmentioning
confidence: 99%
“…40−42 In particular, the systematic designs of sulfur-containing ligands have been investigated in bioinorganic chemistry and for their ability to create various coordination network architectures. 43,44 Following our ongoing research on the development of coordination polymers with S donor ligands, 20,45,46 herein, we report four novel metal−organic frameworks with d 10 transition metals of group 12 and L s (pbit) ligand [where L s or pbit = 1,1′-(pentane-1,5-diyl)bis(-3-methyl-1H-imidazole-2thione)]. The title polymers were applied as an adsorbent for hydrogen sulfide and also used for iodine removal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] It was generally found that the metal centers with the 3d 4 -3d 7 electronic configurations and involved in octahedral coordination surroundings could readily occur spin transition between the different spin states. [26][27][28] Among 3d 4 -3d 7 metal ions, the strong interest has always been devoted to the switchable molecular materials centered with iron(II) ion. During the past several decades, a great deal of the Fe(II)-based complexes with various structure types from 0D clusters, 1D infinite chains to 2-3D networks and interesting SCO properties have been reported.…”
Section: Introductionmentioning
confidence: 99%